Pendekatan dan Fungsi Afektif dalam proses pemblajaran - Frezy Paputungan; Evandri Paputungan (Jurnal Ilmu Pendidikan dan Budaya, 2023)
The role and function of affective in the context of the educational approach. Affective refers to the individual’s emotional dimensions involving feelings, attitudes, and emotional responses to the learning environment. The affective domain is related to attitudes and values, affective is everything related to attitudes, character, behavior, interests, emotions, and values ​​that exist within each individual. If viewed from learning in class, learning outcomes can have an impact on changes in student behavior. Affective is one of the three domains that are targeted in the learning process. The affective dimension is critical to holistic learning planning and suggests some practical strategies that educators can employ to facilitate emotionally positive learning experiences. Affective integration in the learning process can increase motivation, social interaction, and student learning out comes. There are several theories and models that support the role of affect in education, including the theory of intrinsic motivation and the theory of emotional intelligence. Related empirical studies can reveal the positive impact of the affective approach in learning. Taking affective aspects into account in an educational approach can have significant benefits for students, including increased motivation to learn, better social relationships, and higher academic achievement. Affective has been a part of learning in schools for decades. It appears in many different forms such as humanist education, moral development, self-actualization, values ​​education, etc. Affective also appears as a response to various social needs such as the widespread use of drugs and promiscuity.